Rancang Bangun Mesin Pengupas Buah Pinang - Siahaan, Derryl Gabriello; Tianur; Edilla; Hendriko (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Areca nut is classified as a grain that is widely distributed in several areas, especially Riau, especially in the Indragiri Hilir area as the largest betel nut producer in Indonesia. Peeling betel nut skin using a machine is easier and faster than manually peeling betel nut, based on that I am very interested in making a "Design of Areca Peeler". Furthermore, the betel nut peeler machine is planned to be able to accommodate areca nut with a capacity of 2.5 kg with a motor power of 3/4 HP. Based on the problems above, it is necessary to design a semi-mechanical dried betel nut peeler that can still be operated using human power. This betel nut peeler machine uses a blade that is placed horizontally and a slam net as a tool for stripping the betel nut method, which is inserted from the top hooper and then into the slamming net, then peeled by the slashing eye and the peeled betel nut comes out of the net that has been adjusted to the size of the betel nut. areca nut size and then down to the sloping part of the thin plate to separate the fruit and betel rind. In 3 experiments carried out from each load given the maximum dry betel nut stripping with a motor speed of 2793 RPM.